2010
DOI: 10.3174/ajnr.a2120
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of the Optic Nerve Sheath in Patients with Craniospinal Hypotension

Abstract: BACKGROUND AND PURPOSE:Craniospinal hyper-or hypotension leads to morphologic changes in certain intracranial structures. We tested the hypothesis that the amount of CSF in the ONS visible in MR imaging is reduced in patients with CSH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 17 publications
(22 reference statements)
0
19
2
2
Order By: Relevance
“…Due to the invasive nature of testing CSFP, noninvasive measures are desirable. Other techniques that have been explored include IOP measurement, 19 optic nerve sheath width measurement by ultrasonography 20 or MRI, 21,22 and an approach using transcranial Doppler technology. 23 Unfortunately, limitations exist for each of these techniques as well as the technical approach that is being used to estimate CSFP.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the invasive nature of testing CSFP, noninvasive measures are desirable. Other techniques that have been explored include IOP measurement, 19 optic nerve sheath width measurement by ultrasonography 20 or MRI, 21,22 and an approach using transcranial Doppler technology. 23 Unfortunately, limitations exist for each of these techniques as well as the technical approach that is being used to estimate CSFP.…”
Section: Discussionmentioning
confidence: 99%
“…Most interesting, further support for this theory is suggested in studies showing a similar correlation in the opposite direction (ie, a small ONSD value in the setting of decreased intracranial pressure). 14,15 In the pediatric population, Le et al 16 tested bedside sonographic assessment of the ONSD in children admitted to an intensive care unit. In their study, ONSD values of 4.0 mm (for children younger than 1 year of age) and 4.5 mm (for older children) were established as the upper limits of the normal diameter.…”
Section: Discussionmentioning
confidence: 99%
“…
We read with interest the recent article entitled "MR Imaging of the Optic Nerve Sheath in Patients with Craniospinal Hypotension" by Rohr et al 1 In patients with craniospinal hypotension, apart from engorged venous sinuses, enlarged pituitary gland, subdural effusions, and sagging of the brain, the authors have observed a partially or fully collapsed intersheath space of the optic nerves. Such a demonstration is particularly clear in their Fig 3. We would like to draw more attention to changes in the pituitary gland.
…”
mentioning
confidence: 97%